Role of Home Location in Fire Disaster Prevention Management - Adam P. Morris (GoAcademica Research & Publishing, 2021)
Location of home plays an important role in a fire disaster prevention management program. The objective of this management program is to determine the reduction in the number of fires by changing the home location from high to low fire potential. 21 volunteers are asked to participate in the survey. They visited 42 homes. From their experience and subjective opinion, the following results are obtained. The fatalities are reduced from 100 to 17 when the location of the home is changed from high history of low historical areas. Thus, it is concluded that statistically there is a significant reduction in the fatalities as shown below. The above conclusion is supported by the following statistical indicators. The p-score, one tailed t value, and standard deviation are 0.0%, 199.01 and 2.89 respectively.